Photosynthetic directed endosymbiosis to investigate the role of bioenergetics in chloroplast function and evolution - Bidhan Chandra De; Jay Cournoyer; Yang-le Gao; Catherine L. Wallace; Stanley Bram; Angad P. Mehta (Nature Communications)
Abstract Cyanobacterial photosynthesis (to produce ATP and NADPH) might have played a pivotal role in the endosymbiotic evolution to chloroplast. However, rather than meeting the ATP requirements of the host cell, the modern-day land plant chloroplasts are suggested to utilize photosynthesized ATP predominantly for carbon assimilation. This is further highlighted by the fact that the plastidic ADP/ATP carrier translocases from land plants preferentially import ATP. Here, we investigate the preferences of plastidic ADP/ATP carrier translocases from key lineages of photosynthetic eukaryotes including red algae, glaucophytes, and land plants. Particularly, we observe that the cyanobacterial endosymbionts expressing plastidic ADP/ATP carrier translocases from red algae and glaucophyte are able to export ATP and support ATP dependent endosymbiosis, whereas those expressing ADP/ATP carrier translocases from land plants preferentially import ATP and are unable to support ATP dependent endosymbiosis. These data are consistent with a scenario where the ancestral plastids may have exported ATP to support the bioenergetic functions of the host cell.